2017
DOI: 10.4172/2155-6121.1000257
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Histamine H1 Receptor Antagonists on Thioredoxin Production In vitro and In vivo

Abstract: Background: Thioredoxin (TRX), a 12-kDa oxidoreductase enzyme, is well known to be a redox-active protein that regulates reactive oxidative metabolism. TRX is also accepted to be a protein with anti-inflammatory effects and reported to attenuate the development of allergic airway inflammatory diseases such as allergic rhinitis (AR) and asthma. Although histamine H1 receptor antagonists are frequently used for the treatment of AR, the influence of the agents on TRX production is not well understood. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, it may be possible that levocetirizine inactivates ROS through direct scavenging activity or via activation of SOD, the only antioxidant enzyme that can scavenge superoxide [ 30 ]. Interestingly, it has also been shown that levocetirizine enhanced production of thioredoxin, a natural ROS scavenger, in hydrogen peroxide-stimulated macrophages [ 31 ]. Furthermore, levocetirizine may attenuate oxidant generation by reducing alveolar infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it may be possible that levocetirizine inactivates ROS through direct scavenging activity or via activation of SOD, the only antioxidant enzyme that can scavenge superoxide [ 30 ]. Interestingly, it has also been shown that levocetirizine enhanced production of thioredoxin, a natural ROS scavenger, in hydrogen peroxide-stimulated macrophages [ 31 ]. Furthermore, levocetirizine may attenuate oxidant generation by reducing alveolar infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%